Global, regional, and national burden of pancreatic cancer from 1990 to 2021, its attributable risk factors, and projections to 2050: a systematic analysis of the global burden of disease study 2021 - Tianyu Li; Chen Lin; Weibin Wang (BMC Cancer)
Abstract Background The incidence and mortality rates of pancreatic cancer are rising globally. This study examines global and regional trends in pancreatic cancer incidence, Disability Adjusted Life Years (DALYs), and mortality from 1990 to 2021, utilizing data from the most recent Global Burden of Disease (GBD) 2021 database. Methods Data were sourced from the GBD database over the period from 1990 to 2021. Age-standardized rates for incidence, DALYs, and mortality were calculated per 100,000 population. We also calculated the proportion of DALYs and mortality attributable to risk factors. The Bayesian age-period-cohort model was applied to project future trends until 2050. Results Between 1990 and 2021, the global incidence of pancreatic cancer increased significantly, with the number of cases rising from approximately 207,905 to 508,533 and the age-standardized incidence rate (ASIR) increasing from 5.47 to 5.96 per 100,000 population. The global burden of pancreatic cancer, measured in DALYs, rose from 5.21 million to 11.32 million. Mortality rates showed a similar upward trend, with the number of deaths increasing from around 211,613 to 505,752, and the age-standardized mortality rate (ASMR) rising from 5.655 to 5.948 per 100,000 population. Notable increases in ASIR and ASMR were observed in low-middle and low sociodemographic index regions with males experienced higher rates compared to females. Age-standardized DALYs rate (ASDR) and ASMR worldwide were attributable to tobacco smoking, high BMI, and high fasting plasma glucose. Furthermore, our projection model estimates that the ASIR and ASMR of pancreatic cancer will significantly decline, while the ASDR is anticipated to maintain a steady downward trend by 2050. Conclusion This study offers a comprehensive analysis of pancreatic cancer trends, providing crucial insights for public health planning and policy-making. Addressing identified risk factors and targeting high-risk populations are essential for effective strategies to reduce the global burden of pancreatic cancer.